A new species of shallow-water cerianthid (Cnidaria: Anthozoa) from South Africa, with remarks on the genus Ceriantheopsis - Molodtsova, Tina (2011)
A new species of tube anemone Ceriantheopsis austroafricanus n. sp. is described from shallow waters in thevicinity of Cape Town, South Africa. This represents the first report of a benthic cerianthid from South Africanwaters. The cnidom and anatomy of other known species of Ceriantheopsis Carlgren are compared with thoseof the new species, the distributions of the species are mapped and a key provided to their identification.